Multi-element and stable isotopes characterization of commercial avocado fruit (Persea americana Mill) with origin authentication purposes. (July 2022) - Muñoz-Redondo, J.M.; Bertoldi, D.; Tonon, A.; Ziller, L.; Camin, F.; Moreno-Rojas, J.M.
Abstract: Avocado ( Persea americana Mill ) is a fruit consumed worldwide due to its valuable organoleptic and health-promoting properties. To date, no information is available about the isotopic composition of this foodstuff and this study determines the stable isotope composition of five bio-elements (C, N, S, H and O) and the composition profile of 46 macro, micro and trace elements. The stable isotope and elemental profiles were determined in 131 avocados from different producing regions (Spain, Brazil, Chile, Colombia, Kenya, Mexico, Peru, South Africa) collected over three years to study the main geographical differences. A PLS-DA model was performed combining the stable isotopes with the elemental profile, making it possible to distinguish the Spanish from the non-Spanish avocados with a high prediction accuracy (98% correct classification). The results of this study highlight the potential of stable isotope ratios and elemental profiles for tracing the geographical origin of avocados. Graphical abstract: Image 1 Highlights: The potential of stable isotopes tracing the origin of Spanish avocados was revealed. The isotopic composition of avocados was characterized for the first time. The potential of elements tracing the origin of Spanish avocados was revealed. Spanish avocados were identified at low classification errors. Results contribute towards the existence of a potential Spanish PGI of avocado.